Melhoria no processo de produção e transporte de Chrysoperla externa (Hagen, 1861) (Neuroptera: Chrysopidae) para uso no controle biológico aplicado - Amaral, Bruno Barbosa (2015)
In Brazil, Chrysoperla externa (Hagen) is the most studied specie of green lacewing, and can be naturally found in many agricultural ecosystems. These predators have great potential to be employed in the population reduction of many arthropod pests. Therefore, this study aimed at developing and improving C. externa rearing techniques for mass production and transportation for use as a biological control agent. The work was comprised of three trials : developing a simple artificial diet for C. externa larvae as an alternative means for food, replacing the diets normally used, constituted, mainly, of Anagasta kuehniella (Zeller) and Sitotroga cerealella (Olivier) eggs; determining the most appropriate density of adults of this control agent for rearing unit (RU); and evaluating the most suitable materials to be used for shipping and transportation containers for C. externa eggs and larvae, which will serve as a support and shelter. The experiments were conducted in the Insect Biology Laboratory, Department of Entomology, at the Universidade Federal de Lavras (UFLA). Of the five artificial diets tested, that which consisted of in natura chicken liver obtained the best results for feeding larvae of second and/or third instars, replacing the alternative prey, being a viable alternative for the development of the insect. The density of eleven couples per RU was the most satisfactory, providing the highest efficiency in eggs production and in maintaining embryo viability superior to 92%. Thus, the most appropriate adult density for the mass production of C. externa per unit of volume is of 71.4 cm 3 per couple. Regarding the shipping and transportation of the eggs, the best substrates were ground corn cobs, sawdust, vermiculite and wheat germ, with no differences between them and maintaining a viability superior to 94.6%. For the larvae, ground cob and sawdust allowed the highest survival rates, 98.5 and 97.5%, respectively, being more suitable for shipping and transporting these predators.